Medical research versus disease burden in Africa - Confraria, Hugo; Wang, Lili (Research Policy, 2020)
Africa is a continent facing severe, urgent, and often unique health challenges. At the same time, in most African countries, national research funding is very limited and research systems are usually dependant on international research funding and collaboration. Therefore, in this context, there are worries that foreign partners will dominate medical research agendas, which may take research away from being relevant to specific local health needs. In this article, we investigate whether the distribution of medical research priorities and investment in medical research, across diseases in Africa, is related to the disease burden of local populations between 2006 and 2015. Our results show that, although African medical research capacity is still very weak and greatly dependant on public non-African and philanthropic funders, medical research specialisation in sub-Saharan Africa is generally associated with its disease burden. Our results are interesting because they indicate that although there are misalignments at the global level between research priorities and disease burden in absolute terms, in sub-Saharan Africa, there is no clear trade-off between participating in global research networks and producing medical research that is aligned with local health needs.